2018
DOI: 10.1061/(asce)be.1943-5592.0001210
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Assessment of Long-Term Behavior of Prestressed Concrete Box-Girder Bridges

Abstract: Large-span PC box girder bridges suffer excessive vertical deflections and 10 cracking. Recent serviceability failures in china show that, the current modelling approach of 11 the Chinese standard (JTG D62) fails to accurately predict long term deformations of large 12 box girder bridges. This hinders the efforts of inspectors to conduct satisfactory structural 13 assessments and make decisions on potential repair and strengthening. 14 This study presents a model updating approach aiming to assess the models u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…For a statically indeterminate bridge structure, which will experience the process of system transformation during construction, the influence of creep and shrinkage on the structural behavior is more complicated. Of the many analysis methods, the method of step‐by‐step recurrence can easily handle this complex process and can be combined with the existing general finite element method (FEM) software; thus, this method has been widely used in practical engineering . Equation indicates that the creep strain at t n and t n + 1 can be expressed as C(),,tn+1tjσtjC(),,tntjσtj=11dtji=1mai()tjeλi()tntj[]1eλinormalΔtn+1. …”
Section: D Creep and Shrinkage Calculation Model Based On Materials Nmentioning
confidence: 99%
See 3 more Smart Citations
“…For a statically indeterminate bridge structure, which will experience the process of system transformation during construction, the influence of creep and shrinkage on the structural behavior is more complicated. Of the many analysis methods, the method of step‐by‐step recurrence can easily handle this complex process and can be combined with the existing general finite element method (FEM) software; thus, this method has been widely used in practical engineering . Equation indicates that the creep strain at t n and t n + 1 can be expressed as C(),,tn+1tjσtjC(),,tntjσtj=11dtji=1mai()tjeλi()tntj[]1eλinormalΔtn+1. …”
Section: D Creep and Shrinkage Calculation Model Based On Materials Nmentioning
confidence: 99%
“…Owing to their merits in construction, maintenance, and cost, long‐span prestressed concrete (PC) box girder bridges with the balanced cantilever method are widely used around the world. However, such bridges have generally suffered excessive deflection, cracking, and other diseases during their service lives . Bazant et al collected the excessive deflection histories of 56 PC box girder bridges around the world and found that the deflection of the bridges would last for a long time; thus, it was inferred that many other bridges suffer the same issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 1980s and 1990s, researchers focused on the structural analysis [4][5][6][7], since the box girder presented a complex problem. Later, other research topics arose, such as, the structural behavior at different construction stages [3,8], the durability conditions and their effect on the strength conditions [9,10], deflections during construction [11], long-term behavior [12], life-cycle assessment [13,14] and multi-criteria decision making methods applied to the sustainable bridge design [15].…”
Section: Introductionmentioning
confidence: 99%